Financial Viability and Production Efficiency of Piggery Enterprises in Bengaluru, Karnataka, India: A Comprehensive Study - Raghavendra, P. K; Ganapathy, M. S (Archives of Current Research International, 2024)
The present study conducted in Bengaluru, covering Bengaluru urban and rural districts, examined the structure of piggery farms, costs and returns and production efficiency of piggery enterprises. The primary data were collected from 35 piggery farmers, 30 retailers, 10 traders, 5 processors, and 120 consumers. Financial analysis of pig farming in Bengaluru, focusing on a pig fattening and piggery breeding farms. The pig fattening farm, with a 40 average herd size, incurred a total cost of Rs. 5,93,096 /- over 8 months, yielding gross returns of Rs. 7,27,052 /- and net returns of Rs.1,33,955 /-. The financial assessment indicates positive outcomes with a NPW of Rs. 54,981 /- at 12 per cent discount rate, a BCR of 1.23, and an IRR of 14.60 per cent. Similarly, the piggery breeder’s farm, with a herd size of 10 sows and 1 boar, annually demonstrates favourable financial feasibility, generating a net profit of Rs. 2,36,790 /-, NPW of Rs. 1,10,007 /- at 12 per cent discount rate, BCR of 1.31 and an IRR of 17.43 per cent. The production efficiency analyses for both piggery fattening and piggery breeding farms demonstrate positive impacts on efficiency, with significant coefficients for feed, labour, and veterinary care.